ChemInform Abstract: Cycloaddition Chemistry of Tetrafluorothiophene S, S‐Dioxide. Issue 45 (October 2016) - Lemal, David M.
Abstract: Tetrafluorothiophene S, S‐dioxide is found to be an all‐round partner for versatile cycloaddition reactions.